If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(w + -1) = -12 Reorder the terms: 3(-1 + w) = -12 (-1 * 3 + w * 3) = -12 (-3 + 3w) = -12 Solving -3 + 3w = -12 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3w = -12 + 3 Combine like terms: -3 + 3 = 0 0 + 3w = -12 + 3 3w = -12 + 3 Combine like terms: -12 + 3 = -9 3w = -9 Divide each side by '3'. w = -3 Simplifying w = -3
| 4+16x=7x+40 | | ln(9x+80)=ln(8x+71) | | 4(-7n-5)=12+4n | | 2x^2+8x-x-4=18 | | 4x+20=2x+25+x+20 | | 3x+4y=6.8 | | X-512=487 | | 40-6x=-90x+40 | | -53=n+7 | | X^2+2xy=-8 | | 9(4-6)+55= | | -15.00-2.00x=25.00 | | f(x)=5x^2+10x+3 | | -15.00-12.00x=25.00 | | 5.75=3/4x | | -7(r-9)= | | 5(2x+3)=4x-9 | | 6r+5(4r-12)= | | 7+7x=2x+32 | | 85=m-4 | | 43+10n=24n-27 | | (x-4y)dx+(x+2y)dy=0 | | 4.8/2 | | 2.5/465 | | 7(5n+9)+n= | | h(t)=27 | | Log(8)+log(-5x)=1 | | -5m+45=27-7m | | 7x-10=6(11-3x) | | 4x-11=9x-26 | | 18-3=15 | | 5=x-10y |